Effects of supplementation with corn distillers’ dried grains on animal performance, nitrogen balance, and enteric CH4 emissions of young Nellore bulls fed a high-tropical forage diet - Hoffmann, A. [UNESP]; Cardoso, A. S. [UNESP]; Fonseca, N. V.B. [UNESP]; Romanzini, E. P. [UNESP]; Siniscalchi, D. [UNESP]; Berndt, A.; Ruggieri, A. C. [UNESP]; Reis, R. A. [UNESP] (Elsevier, 2021)
The inclusion of corn-dried distillers’ grains (DDG) could be an alternative supplement to increase animal performance, nitrogen efficiency usage (NEU), and decrease enteric methane (CH4) emissions. Our goal was to determine whether DDG could replace a traditional supplement (cottonseed meal) without affecting animal performance, N balance, and CH4 emissions. The experiment was conducted during the forage growing season (December to April), with 15 d adaptation, and a 112 d experimental period. The experimental design was completely randomized with four treatments: a mineral supplement (MS), cottonseed meal supplement (CS), 50% replacement of CS by DDG (50DDG), and 100% replacement of CS by DDG (100DDG). Cottonseed meal and DDG were used as protein supplement. A total of 12 paddocks, 3 per treatment, were used to measure forage mass: morphological and chemical composition of forage, forage allowance, and animal performance. Six animals per treatment were used to evaluate DM intake, digestibility, CH4 emissions, microbial protein production (MCP), and NEU of each treatment. Eighty-one Young Nellore bulls (48 testers, 12 per treatments and 33 adjusters) with initial BW of 255 ± 5 kg (10–12 months old) were supplemented with each supplement type at a level of 0.3% of BW. Pasture management was continuous stocking with a variable stocking rate (put-and-take). Enteric CH4 was measured using the gas tracer technique. The MCP was quantified using purine derivatives and the NEU mass balance. No differences were found in nutrient intake (P > 0.228). Individual animal performance and gain per area were higher in the treatments with concentrates compared with that of MS; however, there was no difference among treatments CS, 50DDG, and 100DDG. The ADG was 0.83 for MS and 1.08 kg/animal/d when supplemented (P < 0.05). Gain per hectare was 709 kg/ha for MS and 915 kg/ha when supplemented with concentrates (P < 0.05). There was no difference in CH4 production among treatments that average 180 g/animal/d; however, CH4 per kg of gain was reduced with CS. The CH4 conversion factor averaged 5.91%. There was no difference in the synthesis of MCP and NEU. Corn DDG can replace 100% of cottonseed meal as a protein source for supplementation of young Nellore bulls grazing in tropical pastures without affecting animal performance, NEU, MCP, and CH4 emissions.
Keywords: Beef cattle; Brachiaria; Diet supplementation; Nitrogen efficiency use; Pasture management